KONSELING KELOMPOK TEKNIK PROBLEM SOLVING UNTUK MENINGKATKAN KEMATANGAN ARAH PILIHAN KARIR SISWA - Wahyuni Wijayanti; Sinta Saraswati (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2020)
Vocational High School, students are students who are vulnerable at the age of 15-18 years, and are at the stage of adolescent development. One of the tasks of adolescent development is the choice and preparation of a career or job. This developmental task is considered important, especially in vocational students who are prepared as graduates ready for work, so that vocational students are very important to have career preparation maturity, but in reality the open unemployment rate of vocational students is more dominates compared to other education level students. The purpose of this study is to provide group problem solving techniques to improve the maturity of the career choices of students. this type of research uses pre experimental design with one group pre-test and post-test research design with a sample of 30 students taken using purposive sampling technique, the data collection tool in this study uses a psychological scale and then analyzed using Wilcoxon analysis techniques. In the analysis, it is known that Asymp.sig (2 tailed) is worth 0.005. Asymp.sig value of 0.008 is smaller than 0.05, it can be concluded that the research hypothesis is accepted. The implication for teacher guidance and counseling is to be an alternative reference in providing group guidance services to help students in career selection.